Determinants of decision-to-intervention time in the management and therapeutic outcome of emergency gynecological surgeries in south east Nigeria - Onyebuchi AK; Lawani LO; Nkwo PO; Iyoke CA; Onoh RC; Ajah LO (Dove Medical Press, 2014)
Azubuike Kanario Onyebuchi,1 Lucky Osaheni Lawani,2 Peter O Nkwo,3 Chukwuemeka Anthony Iyoke,3 Robinson Chukwudi Onoh,1 Leonard O Ajah1 1Department of Obstetrics and Gynecology, Federal Teaching Hospital Abakaliki, Ebonyi State, Nigeria; 2School of Postgraduate Studies, Department of Community Medicine, University of Nigeria, 3Department of Obstetrics and Gynecology, University of Nigeria Teaching Hospital, Enugu, Enugu State, Nigeria Background: Prompt and timely response in the management of gynecological surgical cases can significantly affect the therapeutic surgical outcome of patients in emergency situations. The aim of this study was to evaluate the decision-to-intervention time (DIT), its determinants, and the significance in the therapeutic outcome of emergency gynecological surgeries managed at a federal teaching hospital in south east Nigeria over an 18-month period. Methods: This was a prospective descriptive study of 105 emergency gynecological cases managed at a federal teaching hospital over an 18-month period. Patients were recruited at the point of admission and followed up until discharge for outcome. Data were abstracted with a data entry pro forma and then analyzed with the Epi Info™ statistical software version 7.0. Results: The incidence of gynecological surgical emergencies was 5.1% of the total gynecological cases managed during the study period. The mean DIT was 4.25 (range 1.45–5.50) hours with delay in intervention, mainly due to delays in securing blood/blood products and other materials for resuscitation (46.7%) and a lack of finance (15.2%). Six maternal deaths were recorded, giving a case fatality ratio of 5.7%, while the commonest maternal complications associated with the delays were hemorrhage (61.9%) and the need for blood transfusion (57.1%), respectively. The risk ratio of losing ≥1,000 mL of blood, anemia, hemorrhagic shock, and wound infection in those with DIT ≥120 minutes was statistically greater and significant at 95% confidence interval. Conclusion: Inadequacies in health care services and policies due to poor infrastructure, organizational framework, and financing were the major determinants of the prolonged DIT and therapeutic outcomes. Keywords: determinants, decision-to-intervention time, emergency, therapeutic outcome, gynecological surgeries, clinical risk